Corporate culture survival guide : sense and nonsense about culture change - Schein, Edgar H. (Jossey-Bass Pub. San FranciscoUS, 1999)
Provides guidelines for managers who need to effect corporate change. Defines the ingredients of corporate culture and explains how it influences employee performance. Provides guidance for evaluating an organization's current culture, and for determining whether the culture is compatible with existing or changing corporate circumstances.